Fasting Upregulates npy, agrp, and ghsr Without Increasing Ghrelin Levels in Zebrafish (Danio rerio) Larvae - Opazo, Rafael; Plaza-Parrochia, Francisca; Cardoso dos Santos, Gustavo R.; Carneiro, Gabriel R. A.; Sardela, Vinicius F.; Romero, Jaime; Valladares, Luis (Frontiers in Physiology, 2019)
Food intake in fish and mammals is orchestrated by a hypothalamic crosstalk between orexigenic (food intake stimulation) and anorexigenic (food intake inhibition) signals. Some of these signals are released by peripheral tissues that are associated with energy homeostasis or nutrient availability. During fish larva stage, orexigenic stimulation plays a critical role in individual viability. The goal of this study was to assess the modulation of hypothalamic neuropeptides and peripheral ghrelin through fasting intervention, to enhance the knowledge of the food intake regulation in this critical fish stage. Previously the fasting intervention zebrafish larvae cohort were reared for 20 days post fertilization (dpf) and then randomly divided into two groups of 20 individuals. One group was subjected to a fasting intervention for five days (fasted group), and the other group was fed normally (fed group); this study ware performs in twice independently replicates. At the end of the experiment interventions, individuals from each group and experimental replicate were distributed to assess gene expression, immunohistochemistry, and nLC-HRMS. For relative expression levels, the following genes were selected: neuropeptide Y (npy), agouti-related peptide (agrp), proopiomelanocortin (pomc), cocaine and amphetamine-regulated transcript (cart), ghrelin, ghrelin O-acyltransferase (mboat4) and glucokinase (gck). A significant upregulation of the orexigenic neuropeptides npy and agrp were observed in the fasted group; which also was associated with a significant downregulation of gck. The anorexigenic neuropeptides (pomc and cart) did not show any significant modulation between the groups. However, this orexigenic up-regulations observed in the fasted group could not be associated with a significant ghrelin or goat up-regulation (gene expression) or increase of the ghrelin levels assessed by immunohistochemistry and nLC-HRMS. Our results demonstrate that zebrafish larvae have mature hypothalamic orexigenic responses associated with a fasting challenge at 20 dpf, but without influence of the ghrelin in this reponse. The absence of ghrelin modulation and the upregulation of npy and agrp by fasting intervention suggest that ghrelin is not essential for appetite regulation in the early stages of zebrafish larvae.